2015
DOI: 10.1002/dta.1862
|View full text |Cite
|
Sign up to set email alerts
|

MALDI MSI and LC‐MS/MS: Towards preclinical determination of the neurotoxic potential of fluoroquinolones

Abstract: Fluoroquinolones are broad-spectrum antibiotics with efficacy against a wide range of pathogenic microbes associated with respiratory and meningeal infections. The potential toxicity of this class of chemical agents is a source of major concern and is becoming a global issue. The aim of this study was to develop a method for the brain distribution and the pharmacokinetic profile of gatifloxacin in healthy Sprague-Dawley rats, via Multicenter matrix-assisted laser desorption/ionization mass spectrometry imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…All quinolones appear in the form of [M + H] + in MS, and satisfactory intensity was observed at m/z 352.20, m/z 362.20, m/z 376.18, and m/z 334.19 for LOM, OFL, GAT, and PEF, respectively. And these peaks are basically consistent with the related detection research, 36–38 which proves that CHCA/PPD has the ability and suitability to detect quinolones and sulfonamides without disturbing the molecular structure.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…All quinolones appear in the form of [M + H] + in MS, and satisfactory intensity was observed at m/z 352.20, m/z 362.20, m/z 376.18, and m/z 334.19 for LOM, OFL, GAT, and PEF, respectively. And these peaks are basically consistent with the related detection research, 36–38 which proves that CHCA/PPD has the ability and suitability to detect quinolones and sulfonamides without disturbing the molecular structure.…”
Section: Resultssupporting
confidence: 86%
“…The observed distribution characteristics are consistent with those reported in previous reports. 38,39 In addition to ENR in brain where the content is very low, the concentration levels in other tissues can be calculated using a linear regression curve (Figure S5…”
Section: A Demonstration Of Practical Spatial Distribution Detection ...mentioning
confidence: 99%
“…Our simulations suggested that the optimal plasma AUC value in humans lies somewhere between 10 and 15 mg · h/liter, though the information required to extrapolate this to cerebral DAmB concentrations is not currently available. The application of noninvasive, high-resolution technologies, including matrix-assisted laser desorption ionization–mass spectroscopy imaging (MALDI-MSI), is now possible and offers the exciting potential to elucidate the pharmacokinetic/pharmacodynamic (PK/PD) index associated with efficacy at the site of infection by enabling quantification of drug in specific cerebral sites, as has been demonstrated in murine models that used gatifloxacin ( 37 ), doxycycline ( 38 ), pretomanid ( 39 ), and rifampin ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The precision (%RSD) and accuracy of the analyte in plasma and brain tissue was below 10%, all of which were within the limits set by the EMA (ESI Table 3 †). LC-MS/MS quantication has become the gold standard tool for assessing the concentration proles of a wide range of therapeutics in different biological matrices. 4,[6][7][8]22,[28][29][30][31][32][33] The optimized method was used to determine tissue pK, following a single dose of BDQ over a 24 h period. Quantitative data (LC-MS/MS) of BDQ in plasma and brain tissues following a single dose (25 mg kg À1 ) of i.p.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…1 In the most recent TB drug pipeline, there are several novel agents, many of which are currently undergoing clinical trials to determine their potential against TB. [2][3][4][5][6][7][8] Amongst them, BDQ has proven to be a promising rst-in-class US FDA approved anti-TB agent, which belongs to the diarylquinoline class of antibiotics. BDQ is proposed for the treatment of multidrugresistant tuberculosis (MDR-TB) in combination with other active anti-TB drugs, when an effective therapy regimen could not be established.…”
Section: Introductionmentioning
confidence: 99%